EBSD characterization of the effect of welding parameters on HAZ of AISI409 - Ranjbarnodeha E.; Weissb S.; Hankeb S.; Fischerb A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
One of the main problems during the welding of ferritic stainless steels is severe grain growth in the heat affected zone (HAZ). In the present study, microstructural characteristics of tungsten inert gas (TIG) welded AISI409 ferritic stainless steel were investigated. The effect of the welding parameters on grain size٫ local misorientation and low angle grain boundaries was studied. It was found that the base metal was partly in recrystallization state. Complete recrystallization followed by severe grain growth occurs after joining process due to welding heating cycle. A decrease in the number of low angle grain boundaries in HAZ was observed. Nevertheless, the welding plastic strain increases the density of local misorientation and low angle grain boundaries. This investigation shows that the final state of strain is the result of the competition between welding plastic strains and stress relieving from recrystallization but the decisive factor in determining the grain size in HAZ is heat input.